Inhibition Test of Ethanol from Extract Mangosteen Leaves (Garcinia mangostana L.) as an Acne Antibacterial - Ginting, Junius Gian; Br. Singarimbun, Nurbaiti; Daeli, Mestika Clemesiya Yulianti; Simanjuntak, Helen Anjelina; Purba, Hermawan; Br. Barus, Lydia; Zega, Defcato Firmawati (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
A prevalent global infection that manifests frequently in Indonesia. An example of an infectious disease that is commonly encountered during adolescence is acne (Acne vulgaris). Antibiotics can be used to treat acne; however, their misuse can lead to the development of resistance; therefore, we are searching for inexpensive, readily available alternatives that are also secure. Mangosteen leaves (Garcinia mangostana L.)Â are one alternative to synthetic ingredients when it comes to the treatment of acne. Mangosteen leaves comprise xanthone derivative compounds that exhibit significant biological activity, including antioxidant, antibacterial, and antimicrobial properties. Therefore, this this study aimed to ascertain the inhibitory power of an ethanol extract derived from mangosteen leaves in order to determine its antibacterial activity against Staphylococcus epidermidis bacteria. Additionally, the compound content of the ethanol extract of mangosteen leaves was determined. The inhibition test was conducted by utilizing the paper disc technique, while the extraction method employed the maceration method. As indicated by the phytochemical screening test results, simplicia and ethanol extract of mangosteen leaves were found to contain steroids/triterpenoids, alkaloids, flavonoids, saponins, and tannins. The inhibition test outcomes against Staphylococcus epidermidis bacteria revealed the following: a diameter of 3.3 mm for bacteria at a concentration of 20%, 9.4 mm for bacteria at 40%, 10.4 mm for bacteria at 60%, 12.9 mm for bacteria at 80%, and 13.2 mm for bacteria at 100%